Consumer surplus vs. welfare standard in a political economy model of merger control - Damien J. Neven; Lars-Hendrik Röller (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper considers merger control in a common agency framework where firms and their competitors can influence the antitrust agency and where transparency – while making lobbying less effective – also implies real resource costs. We examine the performance of two alternative standards that can be assigned to the antitrust agency in the presence of these regulatory failures. We find that under a welfare standard, lobbying leads to the clearance of relatively inefficient mergers that decrease welfare (i. e. there is a type II error). By contrast, under a consumer surplus standard, the agency will ban relatively efficient mergers that would increase welfare (i. e. there is a type I error). Lobbying actually reduces the extent to which this occurs, albeit at a cost in terms of real resources. We also find that a consumer surplus standard is more attractive when mergers are large, when increasing the size of a merger greatly enhances industry profits, when there is little transparency, and when co-ordination costs amongst competitors are low. – – In diesem Beitrag wird die wettbewerbsrechtliche Analyse der Fusionskontrolle mit einem Agency-Ansatz erweitert, in dem Unternehmen die Kartellbehörde beeinflussen können und wo Lobbying Kosten verursacht. Es werden zwei unterschiedliche Entscheidungskriterien der Fusionsbehörde hinsichtlich ihrer Effizienz untersucht. Benutzt die Fusionsbehörde ein Wohlfahrtskriterium führt Lobbying seitens der Unternehmen zur Genehmigung von ineffiziente Fusionen, was zu einem Sinken der Wohlfahrt führt. Andererseits führt das Kriterium der Konsumentenrente zur Untersagung von verhältnismäßig effiziente Fusionen, was die Wohlfahrt ebenfalls reduziert. Daraus ergibt sich, daß eine Berücksichtigung der Anreizstrukturen der Unternehmen die Wettbewerbsbehörde zu beeinflussen, wohlfahrttheoretisch keine eindeutige Betrachtungsweise zuläßt. In diesem Sinne zeigt sich, daß das Kriterium der Konsumentenrente vorteilhafter ist, bei Mega-Fusionen, wenn Fusionen sehr profitable sind, wenn es wenig Transparenz gibt und wenn die Koordinationskosten zwischen den nicht-fusionierenden Unternehmen niedrig sind.
Keywords: 330